Modulation of Astrocyte Glutamate Transporters Decreases Seizures in a Mouse Model of Tuberous Sclerosis Complex - Zeng, Ling-Hui (2010)
Astrocyte dysfunction may contribute to epileptogenesis and other neurological deficits in Tuberous Sclerosis Complex (TSC). In particular, decreased expression and function of astrocyte glutamate transporters have been implicated in causing elevated extracellular glutamate levels, neuronal death, and epilepsy in a mouse model of TSC (Tsc1(GFAP)CKO mice), involving inactivation of the Tsc1 gene primarily in astrocytes. Here, we tested whether pharmacological induction of astrocyte glutamate transporter expression can prevent the neurological phenotype of Tsc1(GFAP)CKO mice. Early treatment with ceftriaxone prior to the onset of epilepsy increased expression of astrocyte glutamate transporters, decreased extracellular glutamate levels, neuronal death, and seizure frequency, and improved survival in Tsc1(GFAP)CKO mice. In contrast, late treatment with ceftriaxone after onset of epilepsy increased glutamate transporter expression, but had no effect on seizures. These results indicate that astrocyte glutamate transporters contribute to epileptogenesis in Tsc1(GFAP)CKO mice and suggest novel therapeutic strategies for epilepsy in TSC directed at astrocytes.